Ensuring Water Availability in Surabaya Through Integrated Water Resources Management Implementation - Murti Sari Amalia; Eddy Setiadi Soedjono (Jurnal Teknik ITS, 2019)
Surabaya is inhabited by 3.074.883 lives with majority drinking water comes from local water company (97%). It uses raw water from Surabaya River that is located in the downstream of Brantas River Basin. The streamflow is smaller than upstream because it is used by another water user. Moreover, the pollution load is accumulated so that the degree of treatment is complicated.Brantas River Basin management is needed to ensure water availability, especially in Surabaya. It can be achieved with the implementation of integrated water resources management (IWRM). A survey using in-depth interview (IDI) were conducted to management agency of Brantas River Basin called Jasa Tirta 1 Public Company (Perum Jasa Tirta 1). It will be compared with the principle of IWRM to assess the state of implementation on the Brantas River Basin.The result shows that the management pattern corresponding with IWRM, except for the mitigation of climate change. Climate change influences water availability and sustainability. An important factor in ensuring water availability in Surabaya is the adoption of effective water management. Even though the implementation of IWRM is not complete yet, it can be achieved by making water supply and demand effectively